2023
DOI: 10.3390/jcm12062119
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Decreased Hounsfield Unit Values of Cervical Vertebrae and the Relative Cross-Sectional Area of Flexion/Extension Paraspinal Muscles Are Novel Risk Factors for the Loss of Cervical Lordosis after Open-Door Laminoplasty

Abstract: Open-door laminoplasty is widely used for patients with cervical spondylotic myelopathy (CSM). However, the loss of cervical lordosis (LCL) seems to be unavoidable in the long-term follow-up after surgery, which may affect the clinical outcomes. The risk factors for this complication are still unclear. In this study, patients who underwent open-door laminoplasty between April 2016 and June 2021 were enrolled. Cervical X-rays were obtained to measure the C2–7 Cobb angle, C2–7 sagittal vertical axis (SVA), T1 sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Prior work has demonstrated that HUs are associated with mechanical complications for a variety of procedures involving spinal instrumentation [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] . For example, in their review of patients undergoing thoracolumbar fusions, Pinter et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior work has demonstrated that HUs are associated with mechanical complications for a variety of procedures involving spinal instrumentation [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] . For example, in their review of patients undergoing thoracolumbar fusions, Pinter et al.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, HUs performed better at predicting these failures than typical markers of frailty such as the modified frailty index or Charlson comorbidity index. Similarly, others have recently suggested that HUs are also predictive of screw loosening, [ 5 , 6 ] fracture following fusion, [7] mechanical complications following 3 column osteotomies, [3] and the loss of cervical lordosis following laminoplasty [4] . These works underscore an important association between vertebral HUs and bone quality-related complications, which should be expected given the relationship between HUs and osteoporosis [1] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation